Effect of Potassium Nitrate in ZnO Nanoparticle Synthesis to Study the Performance of Dye Sensitized Solar Cell - Joshi, Leela Pradhan; Bhatta, Jeny; Katuwal, Tika Bahadur; Kafle, Bhim Prasad; Mulmi, Deependra Das (Journal of Institute of Science and Technology, 2019)
X-ray diffraction, Raman investigations, band gap energy of zinc oxide nanoparticles (ZnO NPs) along with current-voltage characteristic curves of an assembled dye-sensitized solar cell (DSSC) are presented in this article. ZnO NPs were first synthesized with and without potassium nitrate (KNO3) salt by precipitation method from precursor solutions of zinc acetate and sodium hydroxide. Then, their thin films were deposited on FTO substrates from the paste made with acetic-acid glacial, and Triton X-100 in ethanol by doctor blade method. The X-ray diffraction (XRD) pattern of ZnO NPs prepared without KNO3 annealed at 500°C showed a hexagonal wurtzite structure with preferred orientation along (101) planes and crystallite size of 25 nm. Very similar XRD pattern was found for ZnO NPs prepared with KNO3. The crystallite size was found decreased to 17 nm for ZnO NPs made with KNO3 salt. Raman spectrum of ZnO NPs showed the presence of E2 high or E2 (2) peak at 437 cm-1. The optical band gaps of the ZnO thin films prepared from ZnO NPs with and without KNO3 were measured to be of 3.16 eV and 3.26 eV, respectively. After sensitizing the above-prepared ZnO films by dye extract of Artocarpus lakoocha, the dye-sensitized solar cells were prepared, and their performance was tested by measuring I-V curves under light illumination of the power density of 1000 W/m2. The measurement showed highest Isc and Voc of 44 μA and 326 mV, respectively.